Rates of Alexithymia and Its Association With Smartphone Addiction Among a Sample of University Students in Egypt - Elkholy, Hussien; Elhabiby, Mahmoud; Ibrahim, Islam (Frontiers in Psychiatry, 2020)
Introduction: Alexithymia is characterized by difficulties describing feelings. Many studies have shown that there is a relation between alexithymia and different types of addictions. Smartphone addiction is suggested to becoming a global problem. The current study focuses on the relation between smartphone addiction and alexithymia in an Egyptian university. Materials and Methods: This is a cross-sectional study that was conducted in Ain Shams University. Measures used includes Smartphone Addiction Scale – Short Version (SAS-SV) and Toronto Alexithymia Scale. Results: results showed that around one third of the sample (N=65, 32.5%) met the criteria of smartphone addiction. The results also showed that 44 students (22%) had alexithymia. There was a strong association between alexithymia and smartphone addiction (OR=4.33, 95% CI: 2.15 - 8.74, p= <0.001). Conclusion: This study supports existing literature of presence of an association between alexithymia and smartphone addiction.